Internal Quality Assurance System in Effort to Improve The Quality of Education - Hadi, Sutarno; Kristiawan, Muhammad; Wardiah, Dessy (Mudir : Jurnal Manajemen Pendidikan, 2023)
This study aims to analyze the implementation of the internal quality assurance system to improve the quality of education at SMP Negeri 9 Prabumulih. This research uses the descriptive-qualitative method. Data collection tools include interviews, observation, documentation, and literature reviews. The results of the research state that (1) the input aspects of SPMI implementation have been fulfilled, but in terms of content quality, several improvements are needed, such as in the development of quality mapping instruments and the preparation of Standard Operational Procedures (SOP) for the implementation of educational services; (2) The aspect of the SPMI implementation process is carried out through 5 stages that form the SPMI cycle, namely standard setting, quality mapping, quality compliance plan, implementation of quality compliance, quality evaluation/audit; (3) The output aspect of SPMI implementation is the fulfillment of the expected goals related to the fulfillment of the 8 SNP (SKL, Content Standards, Process Standards, Assessment Standards, Educators and Education Personnel Standards, Facilities and Infrastructure Standards, Financing Standards and Management Standards) by school management and organizational functioning TPMPS; (4) The outcome aspect of SPMI implementation at Prabumulih 9 Public Middle School is the increasing quality of the learning process and school management in accordance with the SNP; (5) Meanwhile, the Impact aspect of SPMI implementation at Prabumulih 9 Public Middle School is an increase in the quality of learning outcomes, the establishment of a quality culture in schools, the SNP is fulfilled, there is a continuous improvement in the quality of education, the value of accreditation increases each period and the public's trust increases.